Tourist Satisfaction Level of Front Office Department Staff Services at Tanadewa Resort & Spa - Ni Luh Made Sri Trisna Dewi; I Gusti Putu Sutarma; Budi Susanto; I Putu Budiarta (International Journal of Green Tourism Research and Applications, 2021)
The purpose of this study is to analyze customer satisfaction on the service of the front office department staff at Tanadewa Resort & Spa and to describe the indicators that need to be improved and maintained by the front office department staff at Tanadewa Resort & Spa. The sample used in this study were tourists who stayed at Tanadewa Resort & Spa in March - July 2021. The sampling technique used was incidental random sampling with a total sample of 50 respondents. Data were collected by questionnaires distributed to respondents, then the data obtained were processed using SPSS version 26. The analytical techniques used were servqual analysis and Importance Performance Analysis. Servqual is used to analyze the level of tourist satisfaction with services obtained which can be seen from the gap results, while Importance Performance Analysis is used to group service quality indicators into a Cartesian diagram to describe indicators that need to be improved and maintained. The results of this study indicate that customer satisfaction with the service of the front office department staff at Tanadewa Resort & Spa is still not good, because of the 15 service quality indicators there are 9 indicators with negative gap values ​​and 6 indicators having positive gap values. And there are 4 indicators whose performance must be improved and 5 indicators whose performance must be maintained by the front office department staff at Tanadewa Resort & Spa in order to increase customer satisfaction.